A New Fluorogenic Small-Molecule Labeling Tool for Surface Diffusion Analysis and Advanced Fluorescence Imaging of β-Site Amyloid Precursor Protein-Cleaving Enzyme 1 Based on Silicone Rhodamine: SiR-BACE1 - Karch, Sandra; Broichhagen, Johannes; Schneider, Julia; Boening, Daniel; Hartmann, Stephanie; Schmid, Benjamin; Tripal, Philipp; Palmisano, Ralf; Alzheimer, Christian; Johnsson, Kai; Huth, Tobias (Journal of Medicinal Chemistry, 2018)
β-site APP-cleaving enzyme 1 (BACE1) is a major player in the pathogenesis of Alzheimer's disease. Structural and functional fluorescence microscopy offers a powerful approach to learn about the physiology and pathophysiology of this protease. Up to now, however, common labeling techniques require genetic manipulation, use large antibodies, or are not compatible with live cell imaging. Fluorescent small molecules that specifically bind to the protein of interest can overcome these limitations. Herein, we introduce SiR-BACE1, a conjugate of the BACE1 inhibitor S-39 and SiR647, as a novel fluorogenic, tag-free, and antibody-free label for BACE1. We present its chemical development, characterize its photophysical and pharmacologic properties, and evaluate its behavior in solution, in overexpression systems, and in native brain tissue. We demonstrate its applicability in confocal, stimulated emission depletion and dynamic single-molecule microscopy. The first functional studies with SiR-BACE1 on the surface mobility of BACE1 revealed a markedly confined diffusion pattern.
EVALuna2:35761

BACE1 modulates gating of KCNQ1 (Kv7.1) and cardiac delayed rectifier KCNQ1/KCNE1 (IKs) - Agsten, Marianne; Heßler, Sabine; Lehnert, Sandra; Volk, Tilmann; Rittger, Andrea; Hartmann, Stephanie; Raab, Christian; Kim, Doo Yeon; Groemer, Teja W.; Schwake, Michael; Alzheimer, Christian; Huth, Tobias (Journal of Molecular and Cellular Cardiology, 2015)
KCNQ1 (Kv7.1) proteins form a homotetrameric channel, which produces a voltage-dependent K(+) current. Co-assembly of KCNQ1 with the auxiliary ?-subunit KCNE1 strongly up-regulates this current. In cardiac myocytes, KCNQ1/E1 complexes are thought to give rise to the delayed rectifier current IKs, which contributes to cardiac action potential repolarization. We report here that the type I membrane protein BACE1 (?-site APP-cleaving enzyme 1), which is best known for its detrimental role in Alzheimer's disease, but is also, as reported here, present in cardiac myocytes, serves as a novel interaction partner of KCNQ1. Using HEK293T cells as heterologous expression system to study the electrophysiological effects of BACE1 and KCNE1 on KCNQ1 in different combinations, our main findings were the following: (1) BACE1 slowed the inactivation of KCNQ1 current producing an increased initial response to depolarizing voltage steps. (2) Activation kinetics of KCNQ1/E1 currents were significantly slowed in the presence of co-expressed BACE1. (3) BACE1 impaired reconstituted cardiac IKs when cardiac action potentials were used as voltage commands, but interestingly augmented the IKs of ATP-deprived cells, suggesting that the effect of BACE1 depends on the metabolic state of the cell. (4) The electrophysiological effects of BACE1 on KCNQ1 reported here were independent of its enzymatic activity, as they were preserved when the proteolytically inactive variant BACE1 D289N was co-transfected in lieu of BACE1 or when BACE1-expressing cells were treated with the BACE1-inhibiting compound C3. (5) Co-immunoprecipitation and fluorescence recovery after photobleaching (FRAP) supported our hypothesis that BACE1 modifies the biophysical properties of IKs by physically interacting with KCNQ1 in a ?-subunit-like fashion. Strongly underscoring the functional significance of this interaction, we detected BACE1 in human iPSC-derived cardiomyocytes and murine cardiac tissue and observed decreased IKs in atrial cardiomyocytes of BACE1-deficient mice.
EVALuna2:2471

Ion channel regulation by β-secretase BACE1 - enzymatic and non-enzymatic effects beyond Alzheimer's disease - Lehnert, Sandra; Hartmann, Stephanie; Hessler, Sabine; Adelsberger, Helmuth; Huth, Tobias; Alzheimer, Christian (Channels, 2016)
β-site APP-cleaving enzyme 1 (BACE1) has become infamous for its pivotal role in the pathogenesis of Alzheimer's disease (AD). Consequently, BACE1 represents a prime target in drug development. Despite its detrimental involvement in AD, it should be quite obvious that BACE1 is not primarily present in the brain to drive mental decline. In fact, additional functions have been identified. In this review, we focus on the regulation of ion channels, specifically voltage-gated sodium and KCNQ potassium channels, by BACE1. These studies provide evidence for a highly unexpected feature in the functional repertoire of BACE1. Although capable of cleaving accessory channel subunits, BACE1 exerts many of its physiologically significant effects through direct, non-enzymatic interactions with main channel subunits. We discuss how the underlying mechanisms can be conceived and develop scenarios how the regulation of ion conductances by BACE1 might shape electric activity in the intact and diseased brain and heart.
EVALuna2:32820

Kdm6b and Pmepa1 as Targets of Bioelectrically and Behaviorally Induced Activin A Signaling - Link, Andrea; Kurinna, Svitlana; Havlicek, Steven; Lehnert, Sandra; Reichel, Martin; Kornhuber, Johannes; Winner, Beate; Huth, Tobias; Zheng, Fang; Werner, Sabine; Alzheimer, Christian (Molecular Neurobiology, 2016)
The transforming growth factor-? (TGF-?) family member activin A exerts multiple neurotrophic and protective effects in the brain. Activin also modulates cognitive functions and affective behavior and is a presumed target of antidepressant therapy. Despite its important role in the injured and intact brain, the mechanisms underlying activin effects in the CNS are still largely unknown. Our goal was to identify the first target genes of activin signaling in the hippocampus in vivo. Electroconvulsive seizures, a rodent model of electroconvulsive therapy in humans, were applied to C57BL/6J mice to elicit a strong increase in activin A signaling. Chromatin immunoprecipitation experiments with hippocampal lysates subsequently revealed that binding of SMAD2/3, the intracellular effectors of activin signaling, was significantly enriched at the Pmepa1 gene, which encodes a negative feedback regulator of TGF-? signaling in cancer cells, and at the Kdm6b gene, which encodes an epigenetic regulator promoting transcriptional plasticity. Underlining the significance of these findings, activin treatment also induced PMEPA1 and KDM6B expression in human forebrain neurons generated from embryonic stem cells suggesting interspecies conservation of activin effects in mammalian neurons. Importantly, physiological stimuli such as provided by environmental enrichment proved already sufficient to engender a rapid and significant induction of activin signaling concomitant with an upregulation of Pmepa1 and Kdm6b expression. Taken together, our study identified the first target genes of activin signaling in the brain. With the induction of Kdm6b expression, activin is likely to gain impact on a presumed epigenetic regulator of activity-dependent neuronal plasticity.
EVALuna2:2488

?-Secretase BACE1 regulates hippocampal and reconstituted M-currents in a ?-subunit-like fashion - Heßler, Sabine; Zheng, Fang; Hartmann, Stephanie; Rittger, Andrea; Lehnert, Sandra; Voelkel, Meike; Nissen, Matthias; Edelmann, Elke; Saftig, Paul; Schwake, Michael; Huth, Tobias; Alzheimer, Christian (The Journal of Neuroscience, 2015)
The ?-secretase BACE1 is widely known for its pivotal role in the amyloidogenic pathway leading to Alzheimer's disease, but how its action on transmembrane proteins other than the amyloid precursor protein affects the nervous system is only beginning to be understood. We report here that BACE1 regulates neuronal excitability through an unorthodox, nonenzymatic interaction with members of the KCNQ (Kv7) family that give rise to the M-current, a noninactivating potassium current with slow kinetics. In hippocampal neurons from BACE1(-/-) mice, loss of M-current enhanced neuronal excitability. We relate the diminished M-current to the previously reported epileptic phenotype of BACE1-deficient mice. In HEK293T cells, BACE1 amplified reconstituted M-currents, altered their voltage dependence, accelerated activation, and slowed deactivation. Biochemical evidence strongly suggested that BACE1 physically associates with channel proteins in a ?-subunit-like fashion. Our results establish BACE1 as a physiologically essential constituent of regular M-current function and elucidate a striking new feature of how BACE1 impacts on neuronal activity in the intact and diseased brain.
EVALuna2:2474

β-Secretase BACE1 Is Required for Normal Cochlear Function - Dierich, Marlen; Hartmann, Stephanie; Dietrich, Nadine; Möser, Philip; Brede, Franziska; Johnson Chacko, Lejo; Tziridis, Konstantin; Schilling, Achim; Krauß, Patrick; Heßler, Sabine; Karch, Sandra; Schrott-Fischer, Anneliese; et al. (The Journal of Neuroscience, 2019)
Cleavage of amyloid precursor protein (APP) by β-secretase BACE1 initiates the production and accumulation of neurotoxic amyloid-β peptides, which is widely considered an essential pathogenic mechanism in Alzheimer's disease (AD). Here, we report that BACE1 is essential for normal auditory function. Compared with wild-type littermates, BACE1-/- mice of either sex exhibit significant hearing deficits, as indicated by increased thresholds and reduced amplitudes in auditory brainstem responses (ABRs) and decreased distortion product otoacoustic emissions (DPOAEs). Immunohistochemistry revealed aberrant synaptic organization in the cochlea and hypomyelination of auditory nerve fibers as predominant neuropathological substrates of hearing loss in BACE1-/- mice. In particular, we found that fibers of spiral ganglion neurons (SGN) close to the organ of Corti are disorganized and abnormally swollen. BACE1 deficiency also engenders organization defects in the postsynaptic compartment of SGN fibers with ectopic overexpression of PSD95 far outside the synaptic region. During postnatal development, auditory fiber myelination in BACE1-/- mice lags behind dramatically and remains incomplete into adulthood. We relate the marked hypomyelination to the impaired processing of Neuregulin-1 when BACE1 is absent. To determine whether the cochlea of adult wild-type mice is susceptible to AD treatment-like suppression of BACE1, we administered the established BACE1 inhibitor NB-360 for 6 weeks. The drug suppressed BACE1 activity in the brain, but did not impair hearing performance and, upon neuropathological examination, did not produce the characteristic cochlear abnormalities of BACE1-/- mice. Together, these data strongly suggest that the hearing loss of BACE1 knock-out mice represents a developmental phenotype.SIGNIFICANCE STATEMENT Given its crucial role in the pathogenesis of Alzheimer's disease (AD), BACE1 is a prime pharmacological target for AD prevention and therapy. However, the safe and long-term administration of BACE1-inhibitors as envisioned in AD requires a comprehensive understanding of the various physiological functions of BACE1. Here, we report that BACE1 is essential for the processing of auditory signals in the inner ear, as BACE1-deficient mice exhibit significant hearing loss. We relate this deficit to impaired myelination and aberrant synapse formation in the cochlea, which manifest during postnatal development. By contrast, prolonged pharmacological suppression of BACE1 activity in adult wild-type mice did not reproduce the hearing deficit or the cochlear abnormalities of BACE1 null mice.
CRIS-Team Scopus Importer:2019-11-15
Keywords: Alzheimer's disease; auditory function; BACE1; BACE1 inhibitor NB-360; BACE1 knock-out mice; Neuregulin-1

β-Secretase BACE1 Promotes Surface Expression and Function of Kv3.4 at Hippocampal Mossy Fiber Synapses - Hartmann, Stephanie; Zheng, Fang; Kyncl, Michele; Karch, Sandra; Voelkl, Kerstin; Zott, Benedikt; D'Avanzo, Carla; Lomoio, Selene; Tesco, Giuseppina; Kim, Doo Y.; Alzheimer, Christian; Huth, Tobias (Journal of Neuroscience, 2018)
The β-secretase β-site APP-cleaving enzyme 1 (BACE1) is deemed a major culprit in Alzheimer's disease, but accumulating evidence indicates that there is more to the enzyme than driving the amyloidogenic processing of the amyloid precursor protein. For example, BACE1 has emerged as an important regulator of neuronal activity through proteolytic and, most unexpectedly, also through nonproteolytic interactions with several ion channels. Here, we identify and characterize the voltage-gated K+ channel 3.4 (Kv3.4) as a new and functionally relevant interaction partner of BACE1. Kv3.4 gives rise to A-type current with fast activating and inactivating kinetics and serves to repolarize the presynaptic action potential. We found that BACE1 and Kv3.4 are highly enriched and remarkably colocalized in hippocampal mossy fibers (MFs). In BACE1-/- mice of either sex, Kv3.4 surface expression was significantly reduced in the hippocampus and, in synaptic fractions thereof, Kv3.4 was specifically diminished, whereas protein levels of other presynaptic K+ channels such as KCa1.1 and KCa2.3 remained unchanged. The apparent loss of presynaptic Kv3.4 affected the strength of excitatory transmission at the MF-CA3 synapse in hippocampal slices of BACE1-/- mice when probed with the Kv3 channel blocker BDS-I. The effect of BACE1 on Kv3.4 expression and function should be bidirectional, as predicted from a heterologous expression system, in which BACE1 cotransfection produced a concomitant upregulation of Kv3.4 surface level and current based on a physical interaction between the two proteins. Our data show that, by targeting Kv3.4 to presynaptic sites, BACE1 endows the terminal with a powerful means to regulate the strength of transmitter release.SIGNIFICANCE STATEMENT The β-secretase β-site APP-cleaving enzyme 1 (BACE1) is infamous for its crucial role in the pathogenesis of Alzheimer's disease, but its physiological functions in the intact nervous system are only gradually being unveiled. Here, we extend previous work implicating BACE1 in the expression and function of voltage-gated Na+ and K+ channels. Specifically, we characterize voltage-gated K+ channel 3.4 (Kv3.4), a presynaptic K+ channel required for action potential repolarization, as a novel interaction partner of BACE1 at the mossy fiber (MF)-CA3 synapse of the hippocampus. BACE1 promotes surface expression of Kv3.4 at MF terminals, most likely by physically associating with the channel protein in a nonenzymatic fashion. We advance the BACE1-Kv3.4 interaction as a mechanism to strengthen the temporal control over transmitter release from MF terminals.
EVALuna2:35768